(3GdeSeYs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI hGdSdGe Ydi QShd Gddg Udi Gddg Ydjg hSde aGdZQV GNJUGQ GdeefY hJSejg eNJUQg HGdeSQY djSgG Ydi ef bUQJ geJg JfGhdg s
(3BNQgG (B:s
(3hgh OQge hKdGKg hOQge ai QHYg hOQge MUd eKGd GdeGd hRjGOg NeSI YTQ OQge abS Ydi gPg GdCeKdI eG jQO ef CTjGA HjfgG hHGddg JYGdi GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG eNWhW fUa UaMg hfGbUs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs